2010
DOI: 10.1017/s0954422410000259
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and cardiometabolic health: a review of the evidence

Abstract: The cardiometabolic syndrome (MetS) is a clustering of related metabolic abnormalities including abdominal adiposity, insulin resistance, hypertension, dyslipidaemia and increased inflammatory and thrombotic markers, which is linked to increased risk of type 2 diabetes, CVD and overall mortality. Several cross-sectional and prospective studies have shown an association between low vitamin D status, as indicated by concentrations of serum 25-hydroxyvitamin D (s25(OH)D), and increased prevalence of the MetS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 201 publications
(292 reference statements)
3
52
0
3
Order By: Relevance
“…Vitamin D status has been associated with dyslipidemia in some instances, but the literature is conflicting and the evidence base is still gathered (1). Vitamin D is thought to be essential for maintaining adequate levels of apolipoprotein A-1 (the main component of HDL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D status has been associated with dyslipidemia in some instances, but the literature is conflicting and the evidence base is still gathered (1). Vitamin D is thought to be essential for maintaining adequate levels of apolipoprotein A-1 (the main component of HDL).…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional and prospective studies have shown an association between low vitamin D status, as indicated by concentrations of serum 25-hydroxyvitamin D (25(OH)D), and increased prevalence of the metabolic syndrome (MetS) and individual cardiovascular disease (CVD) risk factors (1). A recent systematic review and meta-analysis, using data from eight crosssectional studies, showed that the prevalence of the MetS was reduced by w50% (odds ratio (OR), 0.49; 95% confidence intervals (CIs), 0.38-0.64)) for those with high 25(OH)D concentration (2).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanistic evidence on the effect of vitamin D status on myocardial diseases and CVD risk factors has been expertly reviewed elsewhere (6,7,(18)(19)(20)(21) . To aid the reader, these will only be briefly highlighted here, and interested readers are referred to these comprehensive reviews for detailed explanations.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…These have been reviewed elsewhere in detail (6,7,(18)(19)(20)(21) . In relation to the latter two, recent data on genetic variants in vitamin D metabolism-related genes and those of the BMI (22)(23)(24) , seem to suggest that obesity contributes to vitamin D deficiency and not that vitamin D deficiency causes obesity.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
See 1 more Smart Citation